Association of acculturation and country of origin with self-reported hypertension and diabetes in a heterogeneous Hispanic population - Rodriguez Fátima; Hicks LeRoi S; López Lenny (BMC, 2012)
Abstract Background Hispanics are the fasting growing population in the U.S. and disproportionately suffer from chronic diseases such as hypertension and diabetes. Little is known about the complex interplay between acculturation and chronic disease prevalence in the growing and increasingly diverse Hispanic population. We explored the association between diabetes and hypertension prevalence among distinct U.S. Hispanic subgroups by country of origin and by degree of acculturation. Methods We examined the adult participants in the 2001, 2003, 2005, and 2007 California Health Interview Survey (CHIS). Using weighted logistic regression stratified by nativity, we measured the association between country of origin and self-reported hypertension and diabetes adjusting for participants' demographics, insurance status, socio-economic status and degree of acculturation measured by citizenship, English language proficiency and the number of years of residence in the U.S. Results There were 33,633 self-identified Hispanics (foreign-born: 19,988; U.S.-born: 13,645). After multivariable adjustment, we found significant heterogeneity in self-reported hypertension and diabetes prevalence among Hispanic subgroups. Increasing years of U.S. residence was associated with increased disease prevalence. Among all foreign-born subgroups, only Mexicans reported lower odds of hypertension after adjustment for socioeconomic and acculturation factors. Both U.S.-born and foreign-born Mexicans had higher rates of diabetes as compared to non-Hispanic whites. Conclusions We found significant heterogeneity among Hispanics in self-reported rates of hypertension and diabetes by acculturation and country of origin. Our findings highlight the importance of disaggregation of Hispanics by country of origin and acculturation factors whenever possible.